(untitled) (Research, Society and Development, 2020)
This study has as its theme the relationship between vegetarians and micronutrient deficiency because it understands that the inadequate vegetarian lifestyle adecism may result in a deficiency of essential nutrients. The objective was to conduct an integrative review on vegetarians and the presence of nutritional deficiency. For the selection of the sample, indexed articles were defined from 2015 to 2020, published in national and international journals, available in Portuguese and English. Data collection was performed in the Virtual Health Library (VHL), Lilacs, Scielo, PubMed, and Google Scholar database, using the following descriptors: vegetarian diet, iron, nutritional deficiencies, vitamin deficiency, mineral deficiency, micronutrients, vitamin B12 deficiency and iron deficiency. The search resulted in 32 articles, after the use of inclusion and exclusion criteria there were 10 articles left for analysis, interpretation and discussion. It was observed that among vegetarians there is a nutritional deficiency or deficiency, and this occurs through the increased consumption of phytatis and oxalates, due to the high intake of fibers. It is concluded that vegetarians present nutritional deficit of zinc, calcium, iron, vitamin B12 and vitamin D and that the adequate intake of all nutrients, through a balanced diet, as well as, if there is a need to insert supplementation of any of these micronutrients, through the complete evaluation of the nutritionist is a promising strategy in the prevention of micronutrient deficit in vegetarians.